2022
DOI: 10.1371/journal.pbio.3001777
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of wound healing is regulated by the convergence of mechanical and epigenetic cues

Abstract: Wound healing in the skin is a complex physiological process that is a product of a cell state transition from homeostasis to repair. Mechanical cues are increasingly being recognized as important regulators of cellular reprogramming, but the mechanism by which it is translated to changes in gene expression and ultimately cellular behavior remains largely a mystery. To probe the molecular underpinnings of this phenomenon further, we used the down-regulation of caspase-8 as a biomarker of a cell entering the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Cells were grown to confluency and RNA extracted as described above. For collection of conditioned media from keratinocytes to treat explants, cells were grown in low Calcium E-media as reported previously 58 . Serum free media was added to confluent plates of cells and conditioned media collected after 16 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown to confluency and RNA extracted as described above. For collection of conditioned media from keratinocytes to treat explants, cells were grown in low Calcium E-media as reported previously 58 . Serum free media was added to confluent plates of cells and conditioned media collected after 16 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its role in normal development, DNMT3A positively regulates the expression of genes involved in stem cell proliferation and promotes the expression of genes that drive epidermal differentiation. 46 Bhatt et al 47 demonstrated that after skin injury, cells near the wound edge expressed DNMT3A. Also, the impact of overexpression of DNMT3A has been reported in different cancer cells.…”
Section: Metalloproteinasesmentioning
confidence: 99%
“…Mechanical stretch on fibroblast promotes hypertrophic scar formation through mechanically activated cation channel Piezo1 and thus therapeutic approaches for scars might target the Piezo1 channel . The tension within the epidermis promotes gene expression through DNA methyltransferase 3A (DNMT3A) nuclear translocation, which is a potential regulator of skin repair . In tissue engineering, researchers use mechanical cues to guide cell behavior and tissue formation.…”
Section: Impact On Drug Development and Tissue Engineeringmentioning
confidence: 99%
“… 50 The tension within the epidermis promotes gene expression through DNA methyltransferase 3A (DNMT3A) nuclear translocation, which is a potential regulator of skin repair. 51 In tissue engineering, researchers use mechanical cues to guide cell behavior and tissue formation. By understanding mechanoregulation, scientists can design better scaffolds and culture conditions for growing tissues and organs in the laboratory.…”
Section: Impact On Drug Development and Tissue Engineeringmentioning
confidence: 99%